Guarana, Selenium, and L-Carnitine Supplementation Improves the Oxidative Profile but Fails to Reduce Tissue Damage in Rats with Osteoarthritis - Aline Zuanazzi Pasinato; José Eduardo Vargas; Julia Spanhol da Silva; Joana Grandó Moretto; Cibele Ferreira Teixeira; Verônica Farina Azzolin; Ivana Beatrice Mânica da Cruz; Camile da Rosa Trevisan; Emanuele Cristina Zub; Renato Puga; Verónica Inés Vargas; Grethel León-Mejía; et al. (Antioxidants)
Osteoarthritis (OA) is a progressive joint disease that is commonly managed with palliative drugs, many of which are associated with undesirable side effects. This study investigated the therapeutic potential of a novel supplementation with guarana, selenium, and L-carnitine (GSC) in a rat model of chemically induced OA. Forty male Wistar rats (8–9 weeks old) received intra-articular sodium monoiodoacetate (Mia) to induce OA, and were subsequently treated with GSC. Inflammatory and oxidative stress parameters were analyzed at the end of the experiment. GSC supplementation enhanced endogenous antioxidant defenses, suggesting systemic antioxidant activity. However, no histological improvement was observed. In silico analyses indicated that Mia-induced OA may involve a complex molecular environment that GSC, at the tested dose, failed to modulate at the site of injury. Despite the limited local effects, these findings support the systemic benefits of GSC and highlight the potential of natural compound-based strategies in OA management. Given the adverse effects of conventional pharmacotherapy, the development of alternative, naturally derived treatments remains a promising avenue for future research.